Respiratory viruses, such as 2009 H1N1 influenza virus, could trigger temporal trends in serotypes causing pneumococcal disease. (13th August 2014) - Launes, C.; García‐García, J.‐J.; Triviño, M.; Peris, N.; Pallarés, R.; Muñoz‐Almagro, C.; Grobusch, M.
Abstract In order to determine if the novel influenza A(H1N1)pdm09 was associated with temporal trends of main serotypes causing invasive pneumococcal disease (IPD), we studied 384 episodes of IPD in <18‐year‐old patients from 2007 to 2012. The number of IPD episodes diagnosed during the 2009 pandemic period meant almost one‐third of all the episodes diagnosed in the five included influenza periods (51/156). The number of IPD episodes diagnosed during the 2009 pandemic period meant almost one‐third of all the episodes diagnosed in the five included influenza periods. Most of them occurred in <5‐year‐old children. Serotype 1 was the main serotype detected over the period, except for the 2009 pandemic, when it practically disappeared. Seasonality and viral infections could trigger temporal trends of serotypes causing IPD.